Solid state generators and energy harvesters for waste heat recovery and thermal energy harvesting. (March 2019) - Zabek, D.; Morini, F.
Highlights: Review of practical solid state generators and thermal energy harvesters. Comparison of heat source temperatures and generator power densities. Analysis of recent advances in solid state conversion efficiency and applications. Abstract: This review covers solid state thermal to electrical energy converters capable of transforming low grade heat directly into electricity for waste heat recovery and thermal energy harvesting. Direct solid state heat engines, such as thermoelectric modules and thermionic converters for spatial temperature gradients, are compared with pyroelectric energy harvesters and thermomagnetic generators for transient changes in temperature. Temperature and size limitations along with the maturity of the technologies are discussed based on energy density and temperature range for the different generator technologies. Despite the low energy conversion efficiency with solid state generators, electric power density ranges from 4 nW/mm 2 to 324 mW/mm 2 . The most promising sector to implement changes while reducing the primary energy consumption and saving resources, is the processing industry along with stationary and mobile electronics.